Simulation And Optimization Of Ethylene Glycol Production - Syed Sulaiman, Syed Hussaini (Universiti Sains Malaysia, 2018)
Ethylene glycol production from syngas using gas-phase hydrogenation of dimethyl oxalate on a copper-based catalyst is one of the crucial technologies. Optimization on the conversion, selectivity and yield of industrial scale production is difficult to be done using experimental base approach. Hence, Aspen Plus Version 10 simulation software is used to simulate, test the sensitivity of operating parameter towards conversion, selectivity and yield, and optimize the production of ethylene glycol using RPLUG reactor model with desired end-product characteristics. The simulation results obtained is acceptable since the error calculated for the ethylene glycol production when compared with literature is only 9.17 %. Sensitivity analysis conducted shows that the conversion of dimethyl oxalate and yield of ethylene glycol were maximum at reactor temperature, pressure and hydrogen to dimethyl oxalate mole ratio of 212'C, 29 bar and 46 respectively. Methyl glycolate to dimethyl oxalate mole ratio do not show significant effect on the conversion and yield. Hence, the variable not included in the optimization study. After optimization, the maximum conversion of dimethyl oxalate, selectivity of ethylene glycol and yield of ethylene glycol obtained are 100 %, 98 % and 99.7 % respectively. This reaction has been optimized at 200 'C, 37 bar, 23.6 wt. % of dimethyloxalate concentration and hydrogen to dimethyl oxalate mole ratio of 64.